A Brief History of Economic Growth - حواس, امين (Milev Journal of Research and Studies, 2019)
The purpose of this article is to provide a brief general overview of the process of economic growth over the course of human history. It explores the forces that have generated the transition from stagnation to sustained growth and have contributed to the emergence of the vast contemporary inequality across countries. Furthermore, it highlights the future of global growth over next 50 years and what will happen to the world income distribution.